Aplikasi Sistem Pendukung Keputusan Menentukan Siswa Terbaik Menggunakan Metode SAW - Wijana, Miki; Gumelar, Ryan Cahya; Supriatman, Rian Dwicahya; Muhyidin, Yusuf (Masoem University, 2024)
The research conducted aims to develop a website-based decision support system application that can determine the best students using the Simple Additive Weighting (SAW) Method and developed with the Rapid Application Development (RAD) method. The SAW method was chosen for its simplicity and its ability to accommodate various assessment criteria, including academic grades, attendance, extracurricular participation, and student achievement. The RAD method was used in the development of the system to ensure a rapid development cycle and flexibility in adjusting user needs. The results show that the developed application is able to provide objective and transparent assessment, and simplify the process of determining the best students efficiently. The system also improves accessibility and accuracy in managing assessment data, reduces manual errors, and speeds up decision making. User testing and evaluation showed a high level of satisfaction, with recommendations for additional feature development in the future.